2005
DOI: 10.1136/adc.2004.057620
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of parental support for families with very preterm children: outcome at 5 years

Abstract: Aims: To test the effectiveness of a home based developmental education intervention in improving outcome at 5 years for very preterm infants. Methods: The Avon Premature Infant Project (APIP) is a randomised controlled trial in which the parents of 284 babies born ,33 weeks gestational age received a developmental education programme, a social support intervention, or standard care. A term reference population was also recruited. This study reports outcomes at 5 years (mean age 58 months 15 days) for 187 (66%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 31 publications
2
51
1
5
Order By: Relevance
“…This makes it difficult to distinguish whether there is an effect on motor outcome and, if not, whether the measures are sensitive enough to detect the effects of intervention. Specific motor assessments, such as the Alberta Infant Motor Scale, the TIMP, and the Movement Assessment Battery for Children were used only by individual studies, 26,28,38 and these data could not be pooled for meta-analysis. Lekskulchai and Cole 28 demonstrated a significant effect of intervention using the TIMP with short-term (4mo corrected age) follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it difficult to distinguish whether there is an effect on motor outcome and, if not, whether the measures are sensitive enough to detect the effects of intervention. Specific motor assessments, such as the Alberta Infant Motor Scale, the TIMP, and the Movement Assessment Battery for Children were used only by individual studies, 26,28,38 and these data could not be pooled for meta-analysis. Lekskulchai and Cole 28 demonstrated a significant effect of intervention using the TIMP with short-term (4mo corrected age) follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this is shown by the IHDP [62][63][64][65] and the Avon Premature Infant Project (APIP) studies. 52,53 APIP followed infants in the Avon area of the United Kingdom to an age of 5 years, whereas the IHDP study is the only report of follow-up of interventions in the infant period up to the age of 18 years.…”
Section: Identification Of Relevant Studiesmentioning
confidence: 99%
“…Few studies described the method of randomization in detail. Only three studies 38,[50][51][52][53][62][63][64][65] reported clearly adequate concealment, while in the remainder of the studies this was unclear. Owing to the inability to blind the initial intervention, a blinded assessment of outcome was considered important to minimize bias, and in 21 36,42 -44,46 -49, 52-56,59 -77 of 25 selected studies, blinding of the outcome assessment was specifically undertaken.…”
Section: Identification Of Relevant Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after completion of the intervention, Griffiths Mental Developmental Scale scores were slightly but significantly higher in both intervention groups, but at age five, no differences in cognitive, motor, and behavioural outcome were found between the three groups; 70% of the initial study population was seen in follow-up. 11 Some of the investigators of the Avon Premature Infant project went on and set up the Parent Baby Interaction Program 12 in 2002, which was carried out in seven NICUs in 232 infants <32 weeks gestational age. The Parent Baby Interaction Program provided structured parental support to facilitate attachment, interaction, and to sensitize parents to their baby's cues, and also educated parents in developmental care principles.…”
Section: Methodsmentioning
confidence: 99%